Asesmen Hasil Belajar Berbasis Teknologi - Ahmad Noviansah Nurjanah; Wildan Nuril Ahmad Fauzi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Reporting assessment results is one of the important parts of the assessment process related to the process of informing other interested parties about learning that has occurred or been done. Reporting learning outcomes can also use technology. The use of computer technology becomes an integral part of every learning activity, including its use as an assessment tool in the education section. it is concluded that the reporting of technology-based assessment results, the first of which is a document containing the value and description of learners' learning outcomes (competency achievement) in all subjects, self-development activities, and personality development. Student learning outcomes report is at least filled in at the end of each semester which is a tool to communicate the results/progress of learners between madrasahs/ schools with parents of learners and with other interested parties to know the learning outcomes of learners in a certain period. Then the second in terms of utilization of reports of assessment of learning results can be seen from the aspects of students, parents/guardians, teachers, and madrasahs/schools. The learning result report model includes the form of reports, value recaps, reports, in the preparation of the results of this assessment using Microsoft Exel technology